Culture of life and impact on nursing teaching - Elizalde Ordoñez, Humberto (2021)
Every human being, wherever they are, is always immersed and in a dynamic relationship with the culture that surrounds them, whether they are diverse people or university students, so the mission of teaching is to train people who are aware of their world and what they are capable of doing for it. This essay allowed to elucidate on the culture of life linked to the teaching of nursing, concluding that the destructuring of the pedagogical process of nursing without culture of life, subtracts the spirit of improvement of students with expectations of progress, because ignorance is sometimes considered as the only and unequivocal expression of mastery.